ANALISIS PENERAPAN PROGRAM STOP WORK AUTHORITY (SWA) PADA PEKERJAAN ARSITEKTUR DAN MEP (MECHANICAL, ELECTRICAL, DAN PLUMBING) (STUDI PROYEK APARTEMEN X PT. Y KOTA DEPOK) - Rizal Bahtiar; Baju Widjasena; Ida Wahyuni (Jurnal Kesehatan Masyarakat, 2019)
PT. Y is a construction service company that has a Stop Work Authority (SWA) policy as a form of prevention against work accidents. Based on preliminary survey findings data, there were four incidents of unsafe actions and unsafe conditions that were not given stop work intervention. This shows that there are problems in implementing the Stop Work Authority (SWA) policy. Therefore it is necessary to find the root of the problem so that further alternative solutions to problems can be found related to the implementation of the Stop Work Authority (SWA) policy. The purpose of this study is to describe and find in- depth information about the application of the Stop Work Authority (SWA) program in Architecture and MEP (Mechanical, Electrical, and Plumbing) work in the X Apartment Project PT. Y Depok City with qualitative methods. In this study the sample was selected using purposive sampling to obtain two main informants and seven triangulation informants. The instruments used in this study were in- depth interview guidelines and observation sheets. From the interviews it was found that the project personnel did not fully know the points of the Stop Work Authority (SWA) policy, there were still project personnel who had low expertise in stopping work interventions, project personnel had good motivation due to the encouragement factor from PT. Y and the same background, supervision is considered not optimal because it only focuses on violations of unsafe actions and unsafe conditions, and the use of SWA forms is only done by HSE staff. PT. Y still needs to optimize communication and oversight of the Stop Work Authority (SWA) policy and ensure that all personnel have the knowledge and expertise regarding the provision of stop work interventions.